2020
DOI: 10.1021/acs.chemmater.0c02463
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Lead-Free (Bi,Ce)-Codoped Cs2Ag0.4Na0.6InCl6 Double Perovskites for White Light-Emitting Diodes

Abstract: Lead-free double perovskite phosphors are promising alternatives to lead halide perovskites for wide uses in optoelectronic applications, but suffer from a low quantum efficiency. Here, we propose to enhance the quantum efficiency of orange-emitting Cs 2 Ag 0.4 Na 0.6 InCl 6 :Bi via a codoping strategy. The internal quantum efficiency of Cs 2 Ag 0.4 Na 0.6 InCl 6 :1% Bi phosphor was increased from 89.9% to the record 98.4 and 98.6% by codoping with 1% Ni and 1% Ce, respectively. High-level density functional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 51 publications
4
99
2
2
Order By: Relevance
“…Thanks to the chemical and structural diversity of metal halide perovskite family, various luminescent lead-free metal halide perovskites (LFMHPs) or their variants have been synthesized and characterized based on metal ions such as Bi 3+ , Sb 3+ , In 3+ , Cu + , Sn 2+ , Mn 2+ with crystal dimensionality from 0D to 3D, and some with reduced dimensionality have revealed superior stability compared with their Pb-based counterparts. [28][29][30][31][32][33][34][35][36][37] Some lead-free perovskites or variants such as Bi, Ce-codoped Cs 2 Ag 0.6 Na 0.4 InCl 6 , [37] (C 4 N 2 H 14 Br) 4 SnBr 6 , [38] and (TEBA) 2 SbCl 5 [28] have exhibited high photoluminescence quantum yield (PLQY) of over 80% and been used as downconversion phosphors to achieve white light emission blended with corresponding commercial phosphors. In addition, some analogs with high PLQY and large stokes shifts such as (C 8 H 17 NH 3 ) 2 SnBr 4 , [39] Cs 2 Ag 0.6 Na 0.4 In 0.85 Bi 0.15 Cl 6 , [40] and Rb 2 CuBr 3 [41] have also been studied as X-ray scintillators showing high light yield under X-ray excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the chemical and structural diversity of metal halide perovskite family, various luminescent lead-free metal halide perovskites (LFMHPs) or their variants have been synthesized and characterized based on metal ions such as Bi 3+ , Sb 3+ , In 3+ , Cu + , Sn 2+ , Mn 2+ with crystal dimensionality from 0D to 3D, and some with reduced dimensionality have revealed superior stability compared with their Pb-based counterparts. [28][29][30][31][32][33][34][35][36][37] Some lead-free perovskites or variants such as Bi, Ce-codoped Cs 2 Ag 0.6 Na 0.4 InCl 6 , [37] (C 4 N 2 H 14 Br) 4 SnBr 6 , [38] and (TEBA) 2 SbCl 5 [28] have exhibited high photoluminescence quantum yield (PLQY) of over 80% and been used as downconversion phosphors to achieve white light emission blended with corresponding commercial phosphors. In addition, some analogs with high PLQY and large stokes shifts such as (C 8 H 17 NH 3 ) 2 SnBr 4 , [39] Cs 2 Ag 0.6 Na 0.4 In 0.85 Bi 0.15 Cl 6 , [40] and Rb 2 CuBr 3 [41] have also been studied as X-ray scintillators showing high light yield under X-ray excitation.…”
Section: Introductionmentioning
confidence: 99%
“…found that the PLQY of Cs 2 Ag 0.4 Na 0.6 InCl 6 could be boosted from 89.9% to 98.6% and 98.4% via Bi 3+ ‐Ce 3+ and Bi 3+ ‐Ni 3+ co‐doped, respectively, which were the highest value in the reported HDP materials and exhibited a great potential in solid‐state lighting. [ 76 ]…”
Section: Strategies For Boosting the Efficiency Of Halide Double Peromentioning
confidence: 99%
“…In summary, the metal cation doping/alloying strategies are effective pathways for modulating photoelectric performance of lead‐free HDPs, which can realize the variable bandgap, adjustable electronic structure, enhanced PL intensity, and tunable emission peak and PL excitation peak. Although the HDP bulk materials prepared via metal cation doping are almost the same PLQY as lead halide perovskite nanocrystals, [ 6,67,76 ] the PL properties of lead‐free HDPs nanocrystals still are unsatisfactory for practical commercialization for future solid‐state lightings and displays. Hence, boosting PL properties of HDP nanocrystals by metal doping/alloying strategies still needs further study.…”
Section: Strategies For Boosting the Efficiency Of Halide Double Peromentioning
confidence: 99%
See 2 more Smart Citations